2019
DOI: 10.3389/fpubh.2019.00191
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Undernutrition in Young Children Living in Urban Slums of Mumbai, India: A Cross Sectional Study

Abstract: Background: Young children living in urban slums are vulnerable to malnutrition and subsequently poor health outcomes, but data on the correlates of stunting, underweight, wasting, and anemia specifically among 10–18 month-old children in India remain limited. Objective: In this analysis, we sought to describe the prevalence of and examine correlates for different markers of undernutrition, including stunting, underweight, and anemia among 10–18 month-old children living in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 66 publications
3
33
0
Order By: Relevance
“…In fact, we know that the growth outcome measurement obtained every month for 3 years exhibits 40% of the children had poor growth in the slum area, Vellore. Similar nding of high proportion of children had poor growth in their young age were observed in urban slum in India [11,29,[33][34][35][36][37]. The research nding with the growth data is similar to the existing literature in identifying the subgroup pattern such as "large, catch up, stunting, faltering and average" for the growth outcomes of height, weight, and head circumference.…”
Section: Discussionsupporting
confidence: 74%
“…In fact, we know that the growth outcome measurement obtained every month for 3 years exhibits 40% of the children had poor growth in the slum area, Vellore. Similar nding of high proportion of children had poor growth in their young age were observed in urban slum in India [11,29,[33][34][35][36][37]. The research nding with the growth data is similar to the existing literature in identifying the subgroup pattern such as "large, catch up, stunting, faltering and average" for the growth outcomes of height, weight, and head circumference.…”
Section: Discussionsupporting
confidence: 74%
“…When stratified by sex, these associations were present only in male children. Poor growth outcomes in male children compared to female children have been previously observed (67)(68)(69)(70). Earlier studies in undernourished infants and their microbiota have found lower microbial diversity with stunting (71), underweight and wasting (57), or severe acute malnutrition (30).…”
Section: Discussionmentioning
confidence: 98%
“…Participants were children between 10 and 18 completed months of age living in urban slums of Mumbai, India (including the eastern wards of Khar, Santacruz, and Bandra) who provided informed caregiver consent to be screened for enrollment into the parent study, a randomized controlled nutrition intervention trial (Clinicaltrials.gov ID: NCT02233764) ( 93 ). This exploratory cross-sectional study examined a subset of participants at screening, prior to enrollment ( 67 ).…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with other studies that have found children born later to be susceptible to poorer nutrition and health outcomes. [56][57][58] One explanation for this could be that increasing numbers of children within a household puts strain on food and household resources, impacting the level of care and nutrition provided. 59 These findings emphasise the importance of family planning and reproductive health services that enable women to control when and how many children they have.…”
Section: Child Characteristicsmentioning
confidence: 99%